The Copenhagen adduction exercise effect on sport performance and injury prevention: A systematic review with meta-analysis - Quintana-Cepedal, M.; de la Calle, O.; Diez-Solorzano, P.; Sanchez-Martinez, B.; Crespo, I.; Olmedillas, H. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The popularity of the Copenhagen Adduction Exercise (CAE) has risen in recent years. This review aims to evaluate the available evidence on the isolated use of the CAE for both performance enhancement and injury prevention. This systematic review included prospective interventional studies investigating the effect of the CAE on strength and conditioning and injury prevention outcomes. 15 studies were included, comprising randomized controlled trials (n = 4), cluster-randomized controlled trials (n = 6), and pre-post trials (n = 5). These studies assessed adduction and abduction strength, jump and sprint performance, core endurance, dynamic balance, adductor longus muscle thickness, and the seasonal prevalence of groin injuries. Meta-analyses of within-group changes and between-group comparisons were performed using standardized mean differences (SMDs) and relative risk (RR). The implementation of the CAE yielded large effect sizes for adduction (within-group SMD = 0.72, 95% CI = 0.41 to 1.0; between-group SMD = 0.95, 95% CI = 0.18 to 1.7) and abduction (within-group SMD = 0.92, 95% CI = 0.47 to 1.4; between-group SMD = 0.94, 95% CI = 0.33 to 1.56) strength. Adduction strength adaptations were dependent on the repetitions performed (adherence-adjusted repetitions: p = 0.02; adherence-adjusted weekly repetitions: p = 0.0063). Dynamic balance can also be improved using the CAE (within-group SMD = 3.9). The CAE showed no statistically significant effect on seasonal groin injury prevalence (RR = 0.83, 95% CI = 0.41 to 1.68). There were no additional benefits of the intervention for other performance metrics, and the quality of evidence underpinning all findings was rated as very low. The inclusion of the CAE can be recommended for adductor strength training, although current evidence does not support its use for reducing the risk of sustaining groin injuries.